Perencanaan dan Perancangan Bandung Movieland dengan Pendekatan Desain Berkelanjutan dan Konsep Neo Vernacular - Guntur Putra Pratama; Purnama Sakhrial Pradini (Prosiding Sains dan Teknologi, 2022)
The needs of the film industry are inseparable from the public's need for entertainment. In Bandung itself, many films have been produced by various age groups and there are also Bandung film appreciation awards every year, but the current films are still far behind in quality and there is also no film production container that has good facilities and technology. The method used in this study is a qualitative method, with this method the author seeks data from various sources such as organizational bodies, government, and also from the results of the thesis or final project that has been made to support the content of the final project material. Based on the results obtained from the qualitative method that some of the data were successfully obtained and some of them did not exist, and also the standards for this research are still incomplete from both organizational and government agencies. Based on the results of processing the data obtained, the author made the decision to process the data and also develop it so that the results of this research or final project can still be developed again in the future. Keywords: Film, Data Processing, Development